Electrochemical Properties of La2Mg17/Ni Electrodes Prepared via TiF3-Catalysed Mechanical Milling. (15th June 2015) - Li, T.; Liu, Z.; Zhang, G.; Ruan, F.; Guo, R.; Zhang, J.
Abstract : In order to improve the hydrogen storage capacity of conventional La2 Mg17 electrode alloys, a nanocrystalline/amorphous-structured La2 Mg17 -Ni composite material was produced by high energy ball milling in the presence of TiF3 . Subsequent analysis of the discharge/charge cycle performances of this electrode material revealed that its cycle stability and electrochemical capacity were greatly improved, with the latter reaching a maximum value of 787.07 mAh/g with optimisation of the TiF3 addition. Moreover, a remarkable enhancement in the reversibility of electrochemical reactions on the material's surface was also observed. Hydrogen diffusion coefficients for the material were calculated by means of a potential step method, confirming that TiF3 markedly improves the long-range diffusion of hydrogen within the material.